European Union tools in the fight against terrorist propaganda - Miloš SVRČEK (Košická bezpečnostná revue, 2025)
Terrorist propaganda has no place in European society. In particular, thanks to the cooperation of EU Member States within the Internet Forum, significant progress has been made in recent years in removing terrorist content from the internet. However, speed and effectiveness need to be increased, using a number of tools, to maintain standards in the fight against terrorism. Terrorists misuse the internet to spread their messages, and for this reason, in their 2018 State of the Union address, the then EU leaders presented new rules to remove terrorist content from the internet within one hour. Any online platform that wants to offer its services in the European Union will have clear rules to prevent their services from being misused to spread terrorist content. Strict measures will also be introduced to ensure that only terrorist content is targeted and that freedom of expression online is preserved. For this reason, the European Union has proposed specific rules for terrorist content, which is particularly dangerous for our security and trust in the digital world. What is illegal offline is also illegal online. The EU will continue to actively work towards a safer internet that serves people and is based on our values, and is gradually putting into practice legal and institutional tools to counter terrorist propaganda.